Frequent retrotransposition of endogenous genes in ERCC2-deficient cells derived from a patient with xeroderma pigmentosum - Saki Aoto (Stem Cell Research & Therapy, 2019)
Abstract Background Retrotransposition of protein-coding genes is thought to occur due to the existence of numerous processed pseudogenes in both animals and plants. Unlike retrotransposons including Alu and LINE-1, direct evidence of such retrotransposition events has not been reported to date. Even if such an event occurs in a somatic cell, it is almost impossible to detect it using bulk of cells as a sample. Single-cell analyses or other techniques are needed. Methods In order to examine genetic stability of stem cells, we have established induced pluripotent stem cell (iPSC) lines from several patients with DNA repair-deficiency disorders, such as ataxia telangiectasia and xeroderma pigmentosum, along with healthy controls. Performing whole-exome sequencing analyses of these parental and iPSC lines, we compiled somatic mutations accumulated by the deficiency of DNA repair mechanisms. Whereas most somatic mutations cannot be detected in bulk, cell reprogramming enabled us to observe all the somatic mutations which had occurred in the cell line. Patterns of somatic mutations should be distinctive depending on which DNA repair gene is impaired. Results The comparison revealed that deficiency of ATM and XPA preferentially gives rise to indels and single-nucleotide substitutions, respectively. On the other hand, deficiency of ERCC2 caused not only single-nucleotide mutations but also many retrotranspositions of endogenous genes, which were readily identified by examining removal of introns in whole-exome sequencing. Although the number was limited, those events were also detected in healthy control samples. Conclusions The present study exploits clonality of iPSCs to unveil somatic mutation sets that are usually hidden in bulk cell analysis. Whole-exome sequencing analysis facilitated the detection of retrotransposition mutations. The results suggest that retrotranspositions of human endogenous genes are more frequent than expected in somatic cells and that ERCC2 plays a defensive role against transposition of endogenous and exogenous DNA fragments.